LEGAL EFFORTS FOR REVIEW BY THE PUBLIC PROSECUTION OF THE VERDICT DEATH CRIME BECOMES LIFETIME - Fachri, Irfan (Inspiring Law Journal, 2024)
A cassation decision is a decision that has permanent legal force, therefore if they are still dissatisfied with the cassation decision, the parties can submit legal action for judicial review to the Supreme Court through the district court clerk. A request for review is submitted not only for dissatisfaction with the cassation decision, but also for all court decisions that have obtained permanent legal force, in the sense that district court decisions that are not appealed can be submitted for review, and high court decisions that are not appealed can be requested for review. return. However, legal action for judicial review can only be submitted once. Therefore, if you still want to take legal action, this is closed. When applying for a review, the applicant for review must have new evidence that has never been presented before, and if it was presented at a previous hearing, the decision would be different, or have evidence that the judge made a mistake in applying the law. This type of research uses a normative juridical approach and uses qualitative analysis techniques which are then explained and analyzed using descriptive analytical methods. The type of approach used in writing this thesis is a library research approach, namely by studying books and documents related to the topic of the article and also using a statutory regulatory approach, namely by reviewing existing statutory regulations. related to the topic discussed in this research. A request for reconsideration does not suspend or stop the implementation of a court decision. As long as there is no decision, the request for reconsideration, which can only be submitted once, can be withdrawn. The Supreme Court of the Republic of Indonesia decided the request for judicial review at the first and final levels. This confirms that the application for review is only submitted once, and there is a term known as 'no review above review'. This ambiguity in the judicial review occurs due to the provisions in the Prosecutor's Law which state that the Prosecutor also has the right to submit a PK, in order to overcome the public's sense of justice towards the law. Meanwhile, according to the Judicial Power Law itself, prosecutors do not have the right to carry out PK. The right to submit a PK only rests with the Defendant, his Family and/or Heirs. Related to this research, the proposed PK is related to the change of the death penalty to life imprisonment by the judge as a result of the trial process at the Supreme Court